The Comparison of Refined Sugar Concentration in Hard Candy Nutgrass Extract Formulation (Cyperus rotundus L.): Perbandingan Konsentrasi Gula Halus pada Formulasi Sediaan Permen Keras Ekstrak Rumput Teki (Cyperus rotundus L.) - Roxana Faradibah; Stephanie Artemisia; Fitri Maulida N; Khoizun Husna Humda K; Rosselya Shakina; Fira Rizkia Sundari (Journal Pharmasci (Journal of Pharmacy and Science), 2023)
Pain is an unpleasant sensory and emotional experience due to actual or potential tissue damage. Pain is also a warning form of the danger of tissue damage. One of the people who often experience pain is women, especially during menstruation. Based on the American Family Physician, the incidence of dysmenorrhea throughout the world is still very large, the percentage of the dysmenorrhea incidence in the world is on average more than 50% or ranging from 15.8-89.5% of women in each country. Some women who experience dysmenorrhea take analgesic drugs regularly. Nutgrass (Cyperus rotundus) contains a wide variety of secondary metabolites, one of which is flavonoids, has an analgesics effect. This research was aimed to compare the level of refined sugar in the hard candy formulation of the nutgrass. Extraction of flavonoids from Nutgrass can be done by infusion method. The infusion of Nutgrass was processed into candy preparations. This research was conducted by adding a variety of refined sugar. In the first formulation using refined sugar as much as 47 grams and in the second formulation using refined sugar as much as 62 grams. The research results found that the first formula where the sugar content was lower (47 grams) could not crystallize perfectly, while second formula where the sugar content was higher (62 grams) could crystallize well. Hence, it can be said that the higher refined sugar content can make the candy crystallize well.